An evaluation of quality participation experiences in inclusive recreation programming for adults who have an intellectual disability. Issue 2 (3rd April 2022) - Weissman, Shannon E.; St. John, Laura R.; Khalil, Asma; Tamminen, Katherine A.; Cowie Bonne, Jennifer; Kitchener, Lisa; Arbour-Nicitopoulos, Kelly P.
ABSTRACT: Individuals who have an intellectual and/or developmental disability (IDD) may benefit physically and psychosocially from engaging in recreation. This qualitative description study focused on the Inclusion Resource Team programme, an inclusive municipal recreation programme for adults who have an IDD, and explored elements that may lead to optimal recreation experiences. Interviews were conducted with 4 participants, 6 caregivers, and 11 staff. Guided by the Quality Participation Framework (QPF), a thematic analysis examined factors contributing to quality experiences within the programme. All three environmental conditions (physical, social, programme) and six building blocks (autonomy, belonging, challenge, engagement, mastery, meaning) of the QPF contributed to participants' experiences. Some participants experienced barriers to 'belonging' and 'engagement'. Findings support using the QPF in inclusive recreation for adults who have an IDD. Attention must be given to fostering belonging and engagement and environmental conditions that may contribute to these building blocks are identified.